Impaired Prothrombin Consumption in Bernard-Soulier Syndrome Is Corrected In Vitro by Human Factor VIII - Bellucci, S; Girma, J P; Lozano, M; Meyer, D; Caen, J P (Thrombosis and Haemostasis, 1997)
The Bernard-Soulier syndrome (BSS) is characterized by thrombocytopenia with giant platelets, a prolonged bleeding time with defective platelet adhesion to the subendothelium related to a defect in platelet membrane glycoprotein lb (GPIb) and a decreased prothrombin consumption. The mechanism of the latter abnormality remains unknown. In this study, we showed that this defect was corrected by the addition of purified human factor VIII (FVIII) to blood from four patients with BSS. The correction of prothrombin consumption was almost complete at concentrations between 1.5 and 3 IU/ml of FVIII procoagulant activity (VIII.'C) and partially abolished by a monoclonal antibody which neutralizes VIII:C. This correction was specific for FVIII and was not observed after addition of purified human FIX. It was obtained, in the same magnitude range, with FVIII complexed to von Willebrand factor (vWF) but not with free vWF. These data provide a new insight into the knowledge of the physiological interaction between the platelet membrane and the vWF-FVIII complex facilitating plasma coagulation activation and may lead to helpful therapeutic advances.